Gandhi und Nehru: kontrastierende Visionen Indiens - Rothermund, Dietmar (Geschichte und Gesellschaft, 2005)
In spite of divergent views, Gandhi and Nehru never parted company during India's freedom struggle. Nehru, 20 years junior to Gandhi, was influenced by socialism and hoped for a rapid industrialisation of India. Gandhi stressed development from below in India's villages which Nehru regarded as irredeemably backward. But they overcame their ideological difference while striving for India's freedom. -- After the achievement of independence, Nehru's views prevailed.
Gesehen am 12.01.2021